The regulatory knowledge of tourism promotion by its operators and its relationship with the promotion of sustainable development by local and regional authorities in Tacna. - Muñoz Flores, Julio Fidel (2013)
Tourism better cultural exchange and is a must for visitors  and visited, due to satisfaction given to visitors and the  generation of income in the region visited; still important  to know and apply the set of standards that promote  tourism in Tacna.  However; isolation of the facts is presented with  regulations for the promotion of tourism.  Objetivo: The objective is to relate the incidence of  tourism development normative knowledge by operators  to the promotion of sustainability by the competent  authorities of Tacna.  Method: This research is descriptive-correlational study,  its design is not experimental; the study population was  (17) tour operators of Tacna.  Result: Found that there is a direct and meaningful  relationship.  Conclusion: That between regulatory knowledge to  promote tourism of the operators and the impulse  sustainable development Tacna authorities have a direct  and significant